Ґенеза адаптаційних процесів іноземних студентів в Україні - Северин, Надія Василівна; Северин, Віктор Дмитрович; Лапузіна, Олена Миколаївна (ТОВ "Оберіг", 2021)
Статтю присвячено дослідженню актуальної проблеми адаптації іноземних студентів в Україні. У сучасному мультикультурному світі інтенсивно розвиваються міжнародні культурні, освітні, економічні та політичні відносини. Відбувається зближення наукових, культурних, економічних еліт різних країн та взаємопроникнення культур. Це сприяє зростанню соціальної значущості іноземних мов у процесі розвитку сучасної особистості та суспільства. Зростає потреба у швидкому і якісному вивченні іноземної мови, зокрема й української як іноземної. Здобуття освіти в чужій країні супроводжується цілою низкою проблем, однією з яких є адаптація до нового соціокультурного середовища. Етап довузівської підготовки відіграє важливу роль у подальшому навчанні іноземних студентів в українських університетах, тому проблема адаптації на цьому етапі є найбільш актуальною. Завдання викладачів полягає в тому, щоб зробити культурну, мовну, психологічну та соціальну адаптацію іноземців успішною. Вона має сприяти якісному процесу навчання на основних факультетах за обраною спеціальністю, формуванню особистості майбутнього фахівця. У статті виділено види роботи з іноземними студентами, які допомагають пом’якшити і прискорити їх адаптацію до нового освітнього, мовного та соціокультурного середовища. Важливу роль відіграє позааудиторна робота: екскурсії, культпоходи, відвідування музеїв, театрів, філармонії, спортивні змагання, конкурси, поїздки до інших міст України тощо. Вона сприяє зняттю стресу від зустрічі з новою культурою і освітньою системою, зближенню представників різних країн та культур. Координація дій викладачів різних закладів освіти також є домінантою у створенні комфортних освітніх умов та сприяє успішній адаптації іноземних студентів до культурно-освітнього простору України. У перспективі планується створення Центру міжкультурної комунікації іноземних студентів на факультеті міжнародної освіти Національного технічного університету "Харківський політехнічний інститут", що сприятиме розкриттю їх творчих здібностей і ознайомленню з самобутньою українською культурою. Діяльність Центру допоможе формувати комфортне соціально-психологічне середовище, виховувати толерантне ставлення до представників інших культур і релігій шляхом участі студентів у групових багатонаціональних заходах.

The article is devoted to the research of the topical problem of the adaptation of international students in Ukraine. In the modern multicultural world international cultural, educational, economic and political relations are intensively developing. The scientific, cultural, economic elites of different countries are converging and cultures are interpenetrating. This leads to an increase in the social significance of foreign languages in the development of the modern personality and society. There is a growing need for fast and high-quality learning of a foreign language, including Ukrainian as a foreign language. Getting an education in a foreign country is accompanied by a number of problems, one of which is the social and cultural environment adaptation. The stage of pre-university training plays a major role in the further education of international students in Ukrainian universities, so the problem of adaptation at this stage is the most important. The task of teachers is to make cultural, linguistic, psychological and social adaptation successful. It should contribute to the quality of the learning process at the main faculties in the chosen specialty, and also to the formation of the personality of the future specialist. The article highlights the types of work with international students that help to soften and accelerate their adaptation to the new educational, linguistic, social and cultural environment. Extracurricular work has an important role. There are excursions, culture trips, visits to museums, theaters, philharmonic halls, sports competitions, contests, trips to other cities of Ukraine, etc. It helps to relieve stress from meeting a new culture and education system, to bring together representatives of different countries and cultures. Coordination of actions of teachers of different education institutions is also dominant in creating comfortable educational conditions and contributes to the successful adaptation of international students to the cultural and educational space of Ukraine. In the future, it is planned to create a Center for Intercultural Communication of Foreign Students at the Faculty of International Education of the National Technical University "Kharkiv Polytechnic Institute", which will help to reveal the creative abilities of international students and get acquainted with the original Ukrainian culture. The activities of the Center will help to form a comfortable social-psychological environment, to cultivate a tolerant attitude towards representatives of other cultures and religions through the participation of students in multinational group activities.
Genesis of adaptation processes of foreign students in Ukraine
Keywords: навчальний процес; адаптаційні труднощі; координація; соціокультурне середовище; позааудиторна робота; міжнародна освіта; adaptation difficulties; education system; coordination; social and cultural environment; extracurricular work